Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, \(16x^3+54y^3=2\left(8x^3+27y^3\right)=2\left(2x+3y\right)\left(4x^2-12xy+9y^2\right)\)
b, \(5x^2\left(x-1\right)+10xy\left(x-1\right)-5y^2\left(1-x\right)\)
\(=\left(5x^2+10xy+5y^2\right)\left(x-1\right)=5\left(x^2+2xy+y^2\right)\left(x-1\right)=5\left(x+1\right)^2\left(x-1\right)\)
bổ sung phần a hộ mình
\(=2\left(2x+3y\right)\left(4x^2-12xy+9y^2\right)=2\left(2x+3y\right)\left(2x-3y\right)^2\)
= 2(8x3 + 27y3)
= 2[(2x)3 + (3y)3 ]
= 2(2x + 3y) (4x2 - 6xy + 9y2)
Chúc bạn học tốt!
16x3+54y3 = 2(8x3+27y3)
= 2(2x)3+(3y)3
= 2(2x+3y)(4x2 - 6xy + 9y2)
1.\(16x^3+54y^3=2\left[\left(2x\right)^3+\left(3y\right)^3\right]=2\left(2x+3y\right)\left(4x^2-6xy+9y^3\right)\)
2.\(x^5-3x^4+3x^3-x^2=x^2\left(x^3-3x^2+3x-1\right)=x^2\left(x-1\right)^3\)
3.\(16x-5x^2-3=-5x^2+15x+x-3=-5x\left(x-3\right)+\left(x-3\right)=\left(x-3\right)\left(1-5x\right)\)
4.\(x^2+4x+3=x^2+x+3x+3=x\left(x+1\right)+3\left(x+1\right)=\left(x+1\right)\left(x+3\right)\)
5.\(x^4+4=x^4+4x^2+4-4x^2=\left(x^2+2\right)^2-4x^2=\left(x^2+2-2x\right)\left(x^2+2+2x\right)\)
\(16x^3+54y^3\)
\(=2\left(8x^3+27y^3\right)\)
\(=2\left[\left(2x\right)^3+\left(3y\right)^3\right]\)
\(=2\left(2x+3y\right)\left(4x^2+6xy+9y^2\right)\)
Vậy..
a,X^3-16x =x(x^2-16)
b,y(y-2)-3(y-2)=(y+3).(y-2)
c,x^2+4x+4-y^2=(x+2)^2-y^2=(x+y+2).(x+2-Y)
D,4^2y^3-12x^2y^4+16X^5y^3=4x^2y^2(y-3y^2+4X^3y)
16x3 + 54y3
= 2(8x3 + 27y3)
= 2(2x + 3y)(4x2 - 6xy + 9y2)